Strengthening Teachers’ Knowledge of Students’ Conceptions in Physics - Chopra, Shruti (Voices of Teachers and Teacher Educators, 2022)
Understanding learners’ constructs about various physical phenomena is an essential part of science teacher’s knowledge of teaching. This study explores the entailments of strengthening physics teachers’ knowledge of learners’ conceptions regarding Thermodynamics and Kinetic Theory of Gases by engaging them in collective reflection on their classroom processes and students’ thinking. It was found that despite several years of experience of teaching, the teachers lacked a comprehensive understanding of learners’ alternative conceptions, learning difficulties and pedagogical strategies to address students’ ideas. The goal of the study was to develop a model for teacher learning through a research-based, content-specific approach to promote teaching practices that is more responsive to developing students’ understanding.